PEMBERDAYAAN PETERNAK ITIK PADA KELOMPOK SARIRIEK SEPAKAT UNTUK MENINGKATKAN PENGETAHUAN DAN OPTIMALISASI NUTRISI DI KECAMATAN PADANG GANTING KABUPATEN TANAH DATAR - Robi Amizar; Gita Ciptaan; Mirzah Mirzah; Wizna Wizna (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
This community service activity aims to enhance the knowledge of duck farmers in the Saririek Sepakat group located in Padang Ganting District, Tanah Datar Regency, West Sumatra Province. The main challenge faced by this group is the high cost of feed. The solution offered to address this issue is to improve farmers' knowledge through nutrition optimization by transferring knowledge related to duck nutrition and appropriate technology for the use of probiotics, as well as utilizing local feed ingredients to create affordable and efficient rations. The methods used in this community service activity include observation, counseling and training, and post-training assistance. The participants of the activity consist of 20 members of the Saririek Sepakat group. The counseling provided includes the transfer of knowledge regarding the nutritional needs of ducks, challenges, and solutions related to feed. Demonstrations/training were conducted on the use of Waretha probiotics and the preparation of duck rations from simple ingredients to create efficient and affordable feed. The indicator of increased knowledge among group members is shown by the results of observations on their enthusiasm and understanding of the materials and training provided. The outcome of the community service activity is that the knowledge of group members has successfully increased by optimizing nutritional factors to develop duck farming businesses. A ration combining commercial feed/concentrate, rice bran, and corn with the addition of probiotics has become a solution for affordable feed. The conclusion of the community service activity is the increased knowledge of group members, particularly regarding the optimization of nutritional factors for duck farming in the Saririek Sepakat group.